Os efeitos da informação prévia na triagem auditiva neonatal para dois grupos de puérperas - Torres, Kely Cordeiro de Carvalho (2011)
Introduction: The prenatal care is the adequate moment for pregnant women to get ready for the delivery and for the newborn demands. The Neonatal Hearing Screening (NHS) may be seen as one of these demands and enables early detection and intervention of hearing loss. Objective: To investigate effects of previous information about Neonatal Hearing Screening in two groups of puerperal women. Method: It was a quasi-experimental study and the sample subjects were 10 pregnant women and 10 puerperal women. The pregnant women (Group A) received previous information about NHS during prenatal care and the puerperal women (Group B) didn t receive such intervention. After the NHS, semi-structured interviews were performed with both groups. The interviews were fully transcribed and analyzed according to the Discursive Analysis and the Production of Meaning proposal (Spink,2004). Results: A poor knowledge about NHS was verified in both groups and the results found point that the subjects who received previous information (Group A) presented more positive feelings towards the exam when compared to the group that didn t receive the intervention (Group B). Furthermore, it was possible to observe that the previous information was a mediator of mother participation and of multiplication of knowledge during the performance of NHS. Participants of both groups considered that receiving information before the actual conduct is important. Final Considerations: The previous information provoked positive effects in the group that underwent the intervention (Group A). Despite manifesting feelings of anguish regarding the exam s results, the participants of this group informed that knowing the NHS process, including the first test in the maternity hospital and the possible retest and diagnostic evaluation, is essential. It is necessary to increase the spreading of NHS and the inclusion of speech language pathologists in primary healthcare, with active participation in groups of pregnant women and in preventive actions towards hearing loss. Furthermore, it is important to stress that mother empowerment is only possible from a reformulation of ideas which begins after the receiving of proper information